A Marketing Communication–Based Design of Occupational Health and Safety Campaigns in Traditional Blacksmith Communities in Mekarmaju Tourism Village - Tantra, Tarandhika; Aziz, Elvira; Faris Indriya Himawan, Abdurrahman (Society : Jurnal Pengabdian Masyarakat, 2026)
Traditional blacksmiths in the Mekarmaju Tourism Village face persistent challenges related to low awareness and limited implementation of Occupational Safety and Health (OHS) practices. Production activities are largely conducted in traditional workspaces with minimal ventilation, inadequate fire safety measures, and unstructured workflows, while occupational risks are generally considered normal and manageable through personal precautions. Previous safety interventions have shown limited effectiveness due to cultural norms, low safety literacy, and discomfort with personal protective equipment. To address these challenges, this community engagement project used a marketing communications-based approach to design an OHS campaign framework rather than directly implementing technical interventions. The methodology consisted of field observations and needs assessments, campaign strategy development, and mentoring and conceptual evaluation involving key stakeholders, including blacksmith business owners, workers, village officials, and the Tourism Awareness Group (Pokdarwis). The resulting campaign design emphasized a family-centered narrative, positioning the craftsmen as primary breadwinners whose safety directly impacts family well-being, and used word-of-mouth communication, WhatsApp status content, and visual posters as primary channels. This study concludes that a culturally grounded and communication-driven campaign design offers a viable and contextually appropriate platform for raising OHS (Occupational Safety and Health) awareness in traditional craft communities and provides structured guidance for future implementation and impact evaluation.